2016
DOI: 10.1007/s11113-016-9396-y
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Decision-Making: Household Response to Child Illness in Sub-Saharan Africa

Abstract: We draw upon a framework outlining household recognition and response to child illness proposed by Colvin and colleagues (2013) to examine factors predictive of treatment sought for a recent child illness. In particular, we model whether no treatment, middle layer treatment (traditional healer, pharmacy, community health worker, etc.), or biomedical treatment was sought for recent episodes of diarrhea, fever, or cough. Based on multinomial, multilevel analyses of Demographic and Health Surveys from 19 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…Many people do not have the required aptitude to critically appraise the trustworthiness of claims about the effects of treatments, and often act on them in making choices about treatments [15][16][17][18][19][20][21][22][23][24]. Poorly informed health choices can result in overuse of ineffective or harmful treatments (actions intended to maintain or improve the health of individuals or communities), underuse of effective treatments, waste and unnecessary suffering [25][26][27][28][29]. Making well-informed choices about treatments is especially important in low-income countries, which have few resources to waste and where the repercussions for making poor health choices are likely to be greater [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Many people do not have the required aptitude to critically appraise the trustworthiness of claims about the effects of treatments, and often act on them in making choices about treatments [15][16][17][18][19][20][21][22][23][24]. Poorly informed health choices can result in overuse of ineffective or harmful treatments (actions intended to maintain or improve the health of individuals or communities), underuse of effective treatments, waste and unnecessary suffering [25][26][27][28][29]. Making well-informed choices about treatments is especially important in low-income countries, which have few resources to waste and where the repercussions for making poor health choices are likely to be greater [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The health-seeking behaviour for febrile illness by mothers of U5 children is poor and not commensurate with high burden of fever and malaria in Nigeria, a country with highly favourable climatic conditions for malaria transmission [1,2,4,11,12,13]. The Nigeria Demographic Health Survey 2018 revealed that 29% of mothers with no education had the highest proportion of children with a fever in the previous two weeks [3] and six out of ten mothers sought treatment from private sectors, such as patent medicine vendors and pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers' health seeking behaviour for febrile illness in U5 children is not commensurate with the high malaria burden in Nigeria, a country with favourable climatic conditions for malaria transmission [1,2,4,11,12]. Usually, mothers being the most-at-home in Nigeria take the rst step in seeking treatment for their febrile child [13]. The knowledge and perception of the causes of the fever, and fever as indicator of illness severity may contribute to mothers' decision on how, when, and where to seek treatment advice.…”
Section: Introductionmentioning
confidence: 99%
“…The Nigeria Demographic Health Survey 2018 revealed that 29% of mothers with no education had the highest proportion of children with a fever in the past 2 weeks [3] and six out of ten mothers sought advice from private sectors like patent medicine vendors and pharmacists. Additionally, home selfmedication is a common response of mothers to fever like in other high malaria endemic countries [6,13,11]. Therefore, several factors may in uence mothers to seek care or advice for fever within 48 hours of onset in U5 children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation